2012
DOI: 10.1371/journal.pone.0032189
|View full text |Cite
|
Sign up to set email alerts
|

Large Fragment Pre-S Deletion and High Viral Load Independently Predict Hepatitis B Relapse after Liver Transplantation

Abstract: Hepatitis B virus (HBV) associated end-stage liver diseases are the leading causes of liver transplantation (LT) in Taiwan. Relapse of hepatitis B occurs after LT, raising the risk of graft failure and reducing patient survival. Although several oral antiviral agents have been approved for anti-HBV treatment, lamivudine (LAM) remained to be the most widely used preventive regimen in Taiwan. While several clinical predictors have been identified for hepatitis B relapse, the predictive roles of the histopatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Zimmerman et al demonstrated that hepatitis B immunoglobulin (HBIG) and lamivudine prophylactic antiviral treatment can significantly decrease viral recurrence as well as HCC recurrence, improving the post-transplantation survival rate [40]. Considering the high cost of high dose or long-term HBIG treatment, Wu et al adopted a short-term HBIG prophylaxis protocol in combination with life-long lamivudine therapy in their transplantation center; however, the overall HBV relapse rate was higher compared to other high dose or long term HBIG treatments [41]. Short-term HBIG and life-long lamivudine prophylaxis may only be effective in patients without high viral loads.…”
Section: Antiviral Treatment In Liver Transplantationmentioning
confidence: 99%
“…Zimmerman et al demonstrated that hepatitis B immunoglobulin (HBIG) and lamivudine prophylactic antiviral treatment can significantly decrease viral recurrence as well as HCC recurrence, improving the post-transplantation survival rate [40]. Considering the high cost of high dose or long-term HBIG treatment, Wu et al adopted a short-term HBIG prophylaxis protocol in combination with life-long lamivudine therapy in their transplantation center; however, the overall HBV relapse rate was higher compared to other high dose or long term HBIG treatments [41]. Short-term HBIG and life-long lamivudine prophylaxis may only be effective in patients without high viral loads.…”
Section: Antiviral Treatment In Liver Transplantationmentioning
confidence: 99%
“…The deletions that were recognized in the present study were located in T-cell and B-cell epitopes, which may cause evasion of the virus from immune recognition, as shown to happen naturally by another study [17]. Moreover, deletion of small sequences from a pre-S region is also associated with an occult HBV state in patients with genotype C [17, 26, 27].…”
Section: Discussionmentioning
confidence: 59%
“…Regarding the clinical relevance of pre-S1/S2 deletions with infection outcome, Wu et al [27] demonstrated that large fragment deletions reduced the necro-inflammatory grade in relapsing liver failure, an indication of slower disease progression. As large-fragment deletions were also frequent in the ASC patients in the present study, we hypothesize that reducing the pathogenesis is involved in the establishment of an ASC state.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical outcome as well as the graft survival in HBV LT recipients has been improved. This significant step in LT is particularly an effective strategy of HBIG prophylactic therapy alone or in combination with preoperative antiviral agents followed by indefinite treatment ( 85 ). However, the emergence of nucleot (s) ide resistant mutants in the polymerase and HBIG escape mutants in the surface gene can lead to an adverse clinical outcome and a graft failure.…”
Section: Resultsmentioning
confidence: 99%